PARTISIPASI PETANI JAGUNG DALAM KEGIATAN PENYULUHAN PERTANIAN DI DESA ALEBO KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Sukmawati Abdullah (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The agricultural sector is a significant contributor to the regional and national economies, particularly in South Konawe Regency, which boasts extensive agricultural land and a prominent maize production industry. However, the efficacy of maize production is frequently constrained by deficiencies in knowledge and suboptimal agricultural practices. One of the most crucial endeavors in the field of agricultural development is the provision of extension services, which are designed to enhance the knowledge and expertise of farmers, thereby facilitating enhanced agricultural productivity and quality. The objective of this study is to examine the level of participation of maize farmers in Alebo Village in agricultural extension activities. The population under investigation consisted of all corn farmers, amounting to 164 families. This figure was obtained through the application of simple random sampling to a population of 15% (25 families), and the resulting data was subjected to quantitative analysis. The findings revealed that farmer involvement in corn farming extension activities in Alebo Village, Konda Subdistrict, can be classified into distinct phases. These include participation in planning activities, attendance, active engagement in extension activities, and evaluation of agricultural extension activities. Farmer participation in agricultural extension planning activities is classified as low. The participation of respondents in agricultural extension activities is classified as attendance. The participation of corn farmers in each extension activity is classified as active (participating). The participation of corn farmers in their activeness is also classified as active (participating). Finally, the participation of farmers in the evaluation of extension tends to accept the results of extension activities that they have done. Nevertheless, farmers perceive the presence of agricultural extension workers to be highly beneficial for the implementation of their maize farming practices.